2023
DOI: 10.1038/s41598-022-13650-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics analysis of contrast-enhanced T1W MRI: predicting the recurrence of acute pancreatitis

Abstract: To investigate the predictive value of radiomics based on T1-weighted contrast-enhanced MRI (CE-MRI) in forecasting the recurrence of acute pancreatitis (AP). A total of 201 patients with first-episode of acute pancreatitis were enrolled retrospectively (140 in the training cohort and 61 in the testing cohort), with 69 and 30 patients who experienced recurrence in each cohort, respectively. Quantitative image feature extraction was obtained from MR contrast-enhanced late arterial-phase images. The optimal radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The fact that texture analysis of the pancreas is an important predictor of AP prognosis confirms its significance in the initial diagnosis of patients with CT indication. Previous studies pointed out the relevance of radiomics analyses in the prediction of AP recurrence [19,34,35]. Furthermore, the prediction of AP severity is of high clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that texture analysis of the pancreas is an important predictor of AP prognosis confirms its significance in the initial diagnosis of patients with CT indication. Previous studies pointed out the relevance of radiomics analyses in the prediction of AP recurrence [19,34,35]. Furthermore, the prediction of AP severity is of high clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative imaging features are extracted from digital images in a high-throughput manner and changes in the human body at the tissue, cellular, and gene level can therefore be reflected by radiomics ( 18 , 19 ). Studies have found that radiomics models can be used to evaluate the severity of AP and indicate the prognosis and evolution of pancreatitis ( 20 - 22 ). One previous study developed a computed tomography (CT)-based radiomics nomogram to predict the incidence of PPDM-A, which was a single-center study with a small sample size, and only radiomic features were extracted from unenhanced plain CT images, ignoring potentially valuable information ( 23 ).…”
Section: Introductionmentioning
confidence: 99%